The Effect of Gender and Sex Hormones on Cardiovascular Disease, Heart Failure, Diabetes, and Atrial Fibrillation in Sleep Apnea - Hegner, Philipp; Lebek, Simon; Maier, Lars Siegfried; Arzt, Michael; Wagner, Stefan (Frontiers in Physiology, 2021)
Sleep apnea is a highly prevalent disorder with increasing impact on healthcare systems worldwide. Previous studies have been conducted primarily with male subjects, and prevalence and severity of sleep apnea in women are underestimated. Recent clinical and basic science evidence increasingly points to different mechanisms in men and women with sleep-disordered breathing (SDB). SDB is associated with a variety of comorbidities, including cardiovascular disease, heart failure, diabetes, and atrial fibrillation. In this review, we discuss sex-dependent mechanisms of SDB in select associated conditions to sharpen our clinical understanding of these sex-dependent inherent differences.